SISTEM PREDIKSI TAKARAN PUPUK PADA TANAMAN PADI BERDASARKAN WARNA DAUN MENGGUNAKAN ARDUINO NANO - Nurjannah; Faisal Faisal; Afif (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
The system for deciding the indefinite quantity of N chemical would like maybe a system that's ready to give recommendations on the number of doses of nitrogen fertilizer (urea fertilizer) which will tend to rice plants supported the frequency of rice leaves detected by the detector. this technique was engineered victimization the Arduino nano microcontroller because of the main microcontroller, the TCS 3200 color sensor as the input element, the digital display as the output component, and also the I2C LCD Module as a link between the LCD and the Arduino microcontroller. This style of analysis is qualitative research and experimental research by conducting causative relationship experiments on the conditions of 1 management variable (input) with the conditions of the opposite control variables, then analyzing the output created while not dominant it'll be compared with the output without controlling variables. The results of this analysis may be a system which will give recommendation on the indefinite quantity of N chemical application to rice plants supported the inexperienced leaf green frequency price detected by the sensor. The suggested dosage for nitrogen fertilizer is displayed on the 16x2 digital display in kilo/hour angle units.